Impact of mill type on biomass mill behavior - Williams, Orla; Eastwick, Carol; Lester, Edward; Giddings, Donald; Lormor, Stephen (2015)
With increasing use of biomass in pulverized fuel coal fired power stations, the impact of mill type on biomass size and shape is fundamental in optimizing mill and burner performance. The impact of mill type on the energy consumption, particle size and particle shape of four different biomasses commonly combusted in pulverized fuel boilers was investigated in this paper. Miscanthus, mixed wood, and steam exploded pellets, along with powdered olive cake, were comminuted in a planetary ball mill, Bond ball mill and cutting mill. For pelletized miscanthus, milling showed little impact on the particle size and shape of the pellets, with the milling action only reducing the pellets back to their original particle size distribution. This was also observed for the steam exploded pellets and mixed wood pellets in the cutting mill. For non-densified biomasses, such as olive cake, fines below the screen size should be removed before milling in a hammer mill as they pass straight through the mill, resulting in wasted mill capacity and energy consumption. Pellets should be composed of particles close to the required size for conveyance and combustions, and sphericity and roundness are crucial in determining this size. Olive cake showed the most spherical and round particles, but a coarser milled product size than the steam exploded pellets. Miscanthus and mixed wood pellets showed needle like shape profiles, as well as similar particle size distributions. Optimization of the particle size based on the Stokes shape factor is key to optimizing mill, conveyance and burner performance.